Left ventricular end‐diastolic pressure as an independent predictor of outcome during balloon aortic valvuloplasty. Issue 5 (4th December 2013) - Cubeddu, Roberto J.; Don, Creighton W.; Horvath, Sofia A.; Gupta, Pritha P.; Cruz‐Gonzalez, Ignacio; Witzke, Christian; Inglessis, Ignacio; Palacios, Igor F.
<x xml:space="preserve">Abstract</x> Objectives In this study, we examined the predictive value of the left ventricular end‐diastolic pressure (LVEDP) in patients undergoing balloon aortic valvuloplasty (BAV). Background The LVEDP is a useful indicator of hemodynamic status in patients with severe aortic stenosis. In BAV, decompensated heart failure is associated with worse outcomes. Methods We identified all consecutive patients with severe symptomatic aortic stenosis who underwent retrograde BAV at the Massachusetts General Hospital from 2004 to 2008. Patients were stratified and compared according to their baseline LVEDP into ≤15 mm Hg, 16–20 mm Hg, 21–25 mm Hg, and ≥26 mm Hg. Procedural and in‐hospital outcomes and adverse events were compared. Multivariate logistic regression was used for the adjusted analysis. Results A total of 111 patients with a mean age of 83±11 years underwent BAV. Of these, the LVEDP was ≤15 mm Hg in 29 (26%), 16–20 mm Hg in 41 (37%), 21–25 mm Hg in 16 (14%), and ≥26 mm Hg in 25 (23%) patients. Baseline characteristics were similar among the four groups. Noticeably, patients with high LVEDP levels had significantly higher rates of the combined endpoint of in‐hospital death, myocardial infarction (MI), cardiopulmonary arrest, and tamponade was P = 0.02. Periprocedural MI was more common among those with higher LVEDP (16% vs. 2.3%; P = 0.04). Multivariate analysis revealed LVEDP (OR 1.08, for each mm Hg increase in pressure, 95 % CI 1.02–1.14), small LV chamber size, and New York Heart Association class as independent predictors of adverse outcomes. Conclusions The LVEDP is an important independent predictor of poor in‐hospital outcome during BAV. In these patients, the immediate hemodynamic status may be more important than the baseline left ventricular systolic function. Hemodynamic optimization before or during BAV should be considered and may be beneficial. © 2012 Wiley Periodicals, Inc.